Fragment-Based Screening Maps Inhibitor Interactions in the ATP-Binding Site of Checkpoint Kinase 2 - Silva-Santisteban, M. Cris; Westwood, Isaac M.; Boxall, Kathy; Brown, Nathan; Peacock, Sam; McAndrew, Craig; Barrie, Elaine; Richards, Meirion; Mirza, Amin; Oliver, Antony W.; Burke, Rosemary; Hoelder, Swen; et al. (PLOS ONE, 2013)
Checkpoint kinase 2 (CHK2) is an important serine/threonine kinase in the cellular response to DNA damage. A fragment-based screening campaign using a combination of a high-concentration AlphaScreen™ kinase assay and a biophysical thermal shift assay, followed by X-ray crystallography, identified a number of chemically different ligand-efficient CHK2 hinge-binding scaffolds that have not been exploited in known CHK2 inhibitors. In addition, it showed that the use of these orthogonal techniques allowed efficient discrimination between genuine hit matter and false positives from each individual assay technology. Furthermore, the CHK2 crystal structures with a quinoxaline-based fragment and its follow-up compound highlight a hydrophobic area above the hinge region not previously explored in rational CHK2 inhibitor design, but which might be exploited to enhance both potency and selectivity of CHK2 inhibitors.